Dynamics of toxicity within different compartments of a peri-urban river subject to combined sewer overflow discharges - Becouze-Lareure, C.; Thiebaud, L.; Bazin, C.; Namour, P.; Breil, P.; Perrodin, Y. (The Science of the total environment, 2016)
Combined Sewer Overflows (CSO) in small peri-urban streams and rivers are potentially toxic for their biocenosis. Improving the management of CSO discharges requires better knowledge of their dynamics and toxicity. In view to characterizing this toxicity, we sampled the different compartments (benthic and hyporheic zone) of a peri-urban stream located near the city of Lyon in France. The samples were taken at different distances from a CSO and at three period characteristic of different hydrological conditions. Their toxic effects were assessed by bioassays on the dissolved fraction (D. magna, V. fisheri and B. calyciflorus bioassays) and on the particle fraction (V. fisheri and H. incongruens bioassays). The results highlighted significant toxicity of the particulate fraction for the benthic and hyporheic samples, in particular downstream of the CSO, but with high spatio-temporal variability. This variability can first be attributed to the variability of CSO discharge sampling as a function of season and rainfall, and the dynamics of polluted particles (trapping of transported particles in infiltration zones, mobilization during floods). These parameters play a fundamental role in the distribution of pollutants according to the geomorphology of stream facies. Regarding dissolved pollutants, the chemical exchanges taking place at the “water-sediment” interface trigger the transfer of pollutants from one phase to another, after which the dispersion of these pollutants is governed by hydraulic flows. Finally, critical zones and periods are identified for the peri-urban river toxicity studied: benthic sediments under mean flow downstream; hyporheic sediments after a storm event downstream, close to the CSO. Recommendations are made on the basis of the knowledge obtained to optimize the management of these discharges. [Display omitted] •Ecotoxicological risk in different compartments of a peri-urban river.•A comparative study of upstream and downstream sampling stations under different hydrological conditions.•Relationship between quality of sediments and ecotoxicological tests.•Identification of the most critical zones and periods for the ecotoxicity impact.